Survey among critical care nurses and physicians about delirium management - Nydahl, Peter; Haken, Rebecca von (Nursing in critical care, 2018)
Delirium is a serious complication in patients in intensive care units. Previous surveys on delirium management in daily practice showed low adherence to published guidelines. Aim To evaluate delirium management in nurses and physicians working in intensive care units in German-speaking countries and to identify related differences between nurses and physicians. The study used an open online survey with multiple-choice responses.